A multiple case study on the residential interior space management of selected middle class households in the prevention of unintentional home injury in children age five and below - Nulada, Hannah Faye R.; Gallardo, Mildred M. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This research is a qualitative study, specifically a multiple case study design method which attempted to determine how families prevent unintentional home injuries of children through residential interior space management. This research examined the occurrence of unintentional home injuries in seven (7) Filipino middle-class families who reside in Cainta, Rizal, and Antipolo City, with young family members aged five years and below. The respondents were selected using a nonprobability sampling method specifically, the snowball sampling method. Using an observation guide and guide questions, in-depth interviews which consisted of thirteen (13) close- and open-ended questions, were conducted. Subsequently, ocular observations were also taken via digital camera, for supplementary data. Following transcription and encoding, the data was then tabulated into themes for analysis with the aid of the Haddon Matrix. This framework examined the influences of child factors, injury agents, physical and socio-cultural environment factors in the prevalence of unintentional home injuries. The results showed that the most common unintentional home injuries were abrasions and bruises while the most common injury mechanisms were falls caused by slipping and collision with static objects such as furniture. The findings also showed that the selected families applied injury prevention strategies through practical solutions, immediate and temporary, gained from past experiences, and influenced by interventions such as socioeconomic status. In conclusion, regardless of finances, families were still capable in providing child-friendly spaces. Although injury-free home environments were impossible to attain, selected households could go beyond the practical solutions and be informed about childproofing and safe home design.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Interior architecture -- Philippines; Interior decoration -- Philippines; Children -- Wounds and injuries -- Philippines